Dance and the Music of J. S. Bach, Expanded Edition - Little, Meredith, 1934-; Jenne, Natalie, 1934- (Book collections on Project MUSE., 2001)
Stylized dance music and music based on dance rhythms pervade Bach's compositions. Although the music of this very special genre has long been a part of every serious musician's repertoire, little has been written about it. The original edition of this addressed works that bore the names of dances-a considerable corpus. In this expanded version of their practical and insightful study, Meredith Little and Natalie Jenne apply the same principals to the study of a great number of Bach's works that use identifiable dance rhythms but do not bear dance-specific titles. Part I describes French dance practices in the cities and courts most familiar to Bach. Part II presents the dance forms that Bach used, annotating all of his named dances.